Compostos voláteis, poder odorífero e perfil de aroma de óleo extraído de resíduos do processamento de graviola (Annona muricata L.) - Nogueira, Juliete Pedreira (2015)
The industrialization of soursop (Annona muricata L.) is important for the economy of the North and Northeast regions of Brasil, since it generates income, jobs and strengthen the national economy. However, it also generates waste potentially harmful to the environment, if they do not have appropriate treatment or destination. Thus, the objective of the present research was to explore the use of the processing waste of soursop pulp for the production of aromatic oil. The seeds were dried under a constant flow of air at 45 °C until humidity below 10% in a Pardal PE 100 dryer. The dehydrated material was ground and subjected to cold pressing in an hydraulic press (TECNAL, TE-098 model) under a force of 14 tons. The oil obtained was characterized physical and chemically in relation to its density, refractive index, moisture content, and acid, saponification, iodine and peroxides values. The volatile compounds present in the oil were identified comparatively to the soursop pulp. Volatiles were isolated by HS-SPME using the CAR / PDMS fiber; they were separated into two types of capillary column - HP5-MS (0.25 mm x 30m, 0.25 µm) and DB-Wax (30 m x 0.25 mm, 0 25 µm)-, and identified by GC / MS (Agilent, model 7890A GC / 5975C). The isolation conditions of the oil volatiles were optimized by varying the temperature (30 to 60 °C) and the time (15 to 60 minutes) the fiber was exposed to the sample headspace, using a 22 factorial design with four axial points and 3 repetitions of the central point (DCCR), totalizing 11 assays. The optimized condition was determined using the Desirability function available in the Statistica 12.0 software. The identification of volatiles was performed using the mass spectra available in the library NIST / EPA / NIH (version 2.0, 2008) and the retention indexes obtained experimentally and in the scientific literature. Trained panelists determined the sensory profile of the oil comparatively to the pulp and commercial edible oils of pumpkin and apricot kernels, using the Quantitative Descriptive Analysis. The oil extracted from the seeds of soursop presented moisture equal to 0.15%, density of 0.9479 g.cm-3 , 1.4665 refractive index; acid value of 1.11 mg KOH.g-1 , iodine value of 87.98 cgI2.g-1 , saponification value of 192.89 mg KOH.g-1 and peroxide value of 6.45 meq O2.kg-1 . A total of 58 compounds were identified in oil, of which 16 were esters (representing 67% of the total area in the chromatogram), 12 aldehydes (~8.0%) 10 acids (~ 8.0% ), 10 terpenes (~9.7%), 7 hydrocarbons (1.2%), 2 ketones (~ 1.7%) and 1 alcohol (~ 0.2%), among others. The esters methyl hex-2-enoate, ethyl but-2-enoate, methyl but-2-enoate and methyl hexanoate represented major volatiles both in the oil and in the pulp. The oil odor power oil proved to be more than 35 times superior than that of soursop pulp The odor power of oil was more than 35 times higher than the pulp of soursop; so, dilution of 1.4 ml oil / 100 ml of propylene glycol solution had the same aroma intensity as a solution of 50 mL fresh pulp / 100 ml of an aqueous solution. The solution of 1.4 ml oil / 100 ml of propylene glycol showed the same soursop, sweet, citrus, fruity and refreshing aroma notes present in soursop pulp, although at lower intensities. In the solution containing the oil, prevailed an aroma of "oil" and not soursop. But when compared to commercial oils of pumpkin and apricot seeds, all diluted in propylene glycol, the soursop seed oil showed greater intensity of citrus, fruity and soursop aroma, that generally appeal to consumers. The soursop oil presented lower intensity of undesirable aromas like rancid and heated oil then the other oils. The use of seeds from the soursop processing for the extraction of aromatic oil by cold pressing proved viable, with yield compatible with those of mechanical extraction methods.